PENERAPAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN DI KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU (STUDI KUALITAS PELAYANAN KARTU TANDA PENDUDUK) - Je. Raufur Rahim al-Qadr; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to investigate the implementation of the Pelayanan Administrasi Terpadu Kecamatan (PATEN) in the Kecamatan Kunto Darussalam Kabupaten Rokan Hulu. As for the underlying implementation of these studies are still finding many obstacles in the population in the district administrative services Kunto Darussalam as the vagueness of service time (process and results), hospitality, comfort to the matter of cost. The study is based on theoretical analysis and implementation services. This study uses qualitative research. Unit data analysis by means of interviews to several sources, with data on primary and secondary research. The results of this study indicate that; First, the quality of service PATENT in Kecamatan Kunto Darussalam seen from the aspect of service attitude and procedures have been running well, but from the aspect of service time is less than optimal because of a lack of discipline from the concierge service, and from the aspect of care facilities, especially facilities for the public has not been met yet from the aspect of the service charge has been informed in accordance with the procedures in the District PATEN Kunto Darussalam. second, while the factors that affect the quality of service PATEN in Kecamatan Kunto Darussalam is the factor of communication policy, especially related to the authority to issue the e-ID card, resource factors, disposition and bureaucratic structures that are still unclear authority in issuing the e-ID cards that have an impact on the quality of service in Kecamatan Kunto Darussalam.Keywords: Implementation, PATENTS, Services